2019
DOI: 10.3390/ijms20112683
|View full text |Cite
|
Sign up to set email alerts
|

p63 at the Crossroads between Stemness and Metastasis in Breast Cancer

Abstract: After lung cancer, breast cancer (BC) is the most frequent cause of cancer death among women, worldwide. Although advances in screening approaches and targeted therapeutic agents have decreased BC incidence and mortality, over the past five years, triple-negative breast cancer (TNBC) remains the breast cancer subtype that displays the worst prognosis, mainly due to the lack of clinically actionable targets. Genetic and molecular profiling has unveiled the high intrinsic heterogeneity of TNBC, with the basal-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 121 publications
(150 reference statements)
0
41
0
Order By: Relevance
“…The p63 family members are crucial regulators of cancer and have been found to play an important role in embryonic stem cells [25][26][27] . As reported by several studies, TAp63 suppressed the progression of cancers, and thus be considered as a promising strategy for therapeutics 9,10,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The p63 family members are crucial regulators of cancer and have been found to play an important role in embryonic stem cells [25][26][27] . As reported by several studies, TAp63 suppressed the progression of cancers, and thus be considered as a promising strategy for therapeutics 9,10,28 .…”
Section: Discussionmentioning
confidence: 99%
“…p63 is critical for EGFR-, JUN/FOS-and TGFβ/SMADmediated invasion and gene activation p63 has recently been shown to control epithelial stemness and cell fate specification [34], and its expression has been linked to basal-like breast cancers in correlation with additional basal epithelial markers [33]. Previous work by us and others showed that signaling by EGFR and its ligand HB-EGF can be controlled by p63-and/or JUN-mediated activation of the EGFR and HB-EGF genes [35,39,40].…”
Section: Egfr Signaling Enables and Potentiates Tgfβ Induction Of Ap-mentioning
confidence: 99%
“…TAp63 and ΔNp63 isoforms can have dual, genespecific but opposite, effects on target genes [33], implying that their expression needs to be finely regulated during cancer initiation and progression. ΔNp63 isoform is frequently overexpressed in human malignancies and can regulate oncogenic routes involved in the pathogenesis of breast carcinoma by contributing to proliferation, stemness and survival of breast tumors [34]. Previously, we demonstrated, on a genome-wide scale, that co-activation of RAS and TGFβ signaling via downregulation of mutant p53 can enhance binding of p63 to its genomic sites [35].…”
Section: Introductionmentioning
confidence: 97%
“…It has been also found that FBXW7 targets ΔNp63 for polyubiquitination and subsequent degradation. ΔNp63 is highly expressed in the majority of SCC where it acts as an oncogene by regulating specific transcriptional programs aimed to sustain malignant cell proliferation, stemness and survival [ 116 , 117 , 118 , 119 , 120 ]. In a large panel of human cancer cell lines and patient biopsies, FBXW7 abundance was positively correlated with sensitivity to HDAC inhibitors (HDACi), which are known to downregulate ΔNp63 through FBXW7 to induce a tumor-suppressive program [ 121 ].…”
Section: Crls and Scc Etiologymentioning
confidence: 99%